A Christmas Carol - Dickens, Charles (Ladybird Books Ltd, 1982)
Scrooge was the meanest man in the world.He hated everybody and everything- especially Christmas. Then one cold Christmas Eve,three Spirits came to visit him,and his life changed...
Keywords: Juvenile literature-Fiction